How does Industry 4.0 affect international exposure? The interplay between firm innovation and home-country policies in post-offshoring relocation decisions. Issue 4 (August 2022) - Barbieri, Paolo; Boffelli, Albachiara; Elia, Stefano; Fratocchi, Luciano; Kalchschmidt, Matteo
Abstract: This paper investigates whether and how Industry 4.0 innovation intensity, which is developed through patenting and which provides a firm-specific ownership advantage, relates to "relocation of second degree" (RSD) of manufacturing activities, i.e. the movement of previously offshored activities to either the home country (RHC) or a third country (RTC), thus representing a reconfiguration of the firm's extant international exposure. Moreover, we analyse the role of Industry 4.0 policies adopted in the home country, which offers a location advantage that can possibly moderate this relationship. Our findings, based on a sample of 118 RSDs implemented by European companies, reveal that both Industry 4.0 innovation intensity (at the firm level) and policies (at home-country level) have an impact, with the former pushing firms towards RTC, unless the latter are in place at the home country, thus showing the pivotal role of Industry 4.0 policies in re-attracting Industry 4.0 innovative companies in their country of origin. Highlights: Firms developing Industry 4.0 innovations are able to develop a strong ownership advantage that can be exploited abroad. Hence, when revising their offshoring location decisions, these firms tend to keep or expand their international exposure. However, they are more likely to de-internationalize if their home country has an Industry 4.0 policy in place